Resumen guía de práctica clínica para la valoración urológica pretrasplante renal (2018)
In Colombia, exist a significant increase in the number of patients with terminal chronic kidney disease (CKD), up to 23,914 patients in 2014 according to statics of the national health institute. This means an increase in the number of transplants, from 12.5% in 2008 to 18% in 2014 from the overall patients with terminal CKD. Considering that kidney transplant is the best option to those patients, it became of extreme importance to unify criteria and concepts based in the best available evidence to reduce complications and negative effects from the therapy. For these reasons we have created this guideline. Copyright © 2018, Sociedad Colombiana de Urología.